2022
DOI: 10.1088/1742-6596/2267/1/012112
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology: its scope in agriculture

Abstract: The growth in human population is estimated to reach 9.8 billion by mid-2050. To meet the food requirements, reducing the judicious use of fertilizers, agrochemicals and their impact on environment, soil, water, humans and the surrounding biodiversity we have to shift towards sustainable methods. Nanotechnology is one such technology that will help in crop production by improving the input use efficiency by minimizing their losses, site-specific, controlled delivery of fertilizers or agrochemical as per the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…; (b) organic materials developed from active ingredients that have been encapsulated in an organic nanocarrier derived from protein, polymers, lipids, etc. ; and (c) hybrid nanomaterials encompassing both organic and inorganic materials [44][45][46]. Thus, nanomaterials for assembling nanoherbicides can be grouped into three types as discussed below.…”
Section: Types Of Nanomaterials For Assembling Nanoherbicidesmentioning
confidence: 99%
“…; (b) organic materials developed from active ingredients that have been encapsulated in an organic nanocarrier derived from protein, polymers, lipids, etc. ; and (c) hybrid nanomaterials encompassing both organic and inorganic materials [44][45][46]. Thus, nanomaterials for assembling nanoherbicides can be grouped into three types as discussed below.…”
Section: Types Of Nanomaterials For Assembling Nanoherbicidesmentioning
confidence: 99%
“…Nanotechnology is regarded as an effective tool for managing a wide range of environmental stresses by providing novel and practical solutions. Nano-fertilizers (NFs) considerably increase plant growth efficiency, soil quality, and crop yield of high-quality fruits and cereals [59], and also, may serve as a sustainable strategy to promote agricultural yield in (semi-) arid regions [60]. NFs have the potential to improve nutrient absorption and plant output by modulating fertilizer availability in the rhizosphere, prolong stress tolerance by enhancing nutritional capacity, and raise plant defense mechanisms.…”
Section: The Effect Of Nanofertilizer On Crop Yieldmentioning
confidence: 99%
“…Stimulatory effects were seen on total chlorophyll (0.93 g/kg FW), shoot biomass (2168 kg/ha), and essential oil content (3.4 g/kg) and yield (7.4 kg/ha) as a result of sub-risky levels of Zn in nanoform absorption (amounted to an average of 152.6 mg Zn/kg after foliar application of 160 mg of zinc oxide nanoparticles) in comparison with ZnS treatment or control. Foliar application of 160 mg/L ZnO NPs is recommended for optimal micronutrient Zn biofortification, biomass production, and essential oil yield in dragonhead [60]. The researchers used many nanocomposites with different concentrations on different plant species to study their effect on their production and increase the yield [4].…”
Section: The Effect Of Nanofertilizer On Crop Yieldmentioning
confidence: 99%
“…This is a reason being their ability to synchronize the release of nutrients, such as nitrogen and phosphorus, with increases in yield and production of crops, while simultaneously decline the amount of fertilization inputs [El-Bialy et al, 2023]. Due to the ability of consistent and slow release of nutrients, nanofertilizers can enhance nutrient use efficiency (NUE) and help plants to uptake nutrients easily [Reddy and Chhabra, 2022]. Recent studies have reported significant improvements in crop production with 30% increases crop yield compared with conventional fertilizers input [Mandal et al, 2021;Weber et al, 2021].…”
Section: Introductionmentioning
confidence: 99%